Store Operated Calcium Entry in Cell Migration and Cancer Metastasis - Ayat S. Hammad; Khaled Machaca (Cells, 2021)
Ca2+ signaling is ubiquitous in eukaryotic cells and modulates many cellular events including cell migration. Directional cell migration requires the polarization of both signaling and structural elements. This polarization is reflected in various Ca2+ signaling pathways that impinge on cell movement. In particular, store-operated Ca2+ entry (SOCE) plays important roles in regulating cell movement at both the front and rear of migrating cells. SOCE represents a predominant Ca2+ influx pathway in non-excitable cells, which are the primary migrating cells in multicellular organisms. In this review, we summarize the role of Ca2+ signaling in cell migration with a focus on SOCE and its diverse functions in migrating cells and cancer metastasis. SOCE has been implicated in regulating focal adhesion turnover in a polarized fashion and the mechanisms involved are beginning to be elucidated. However, SOCE is also involved is other aspects of cell migration with a less well-defined mechanistic understanding. Therefore, much remains to be learned regarding the role and regulation of SOCE in migrating cells.